2015
DOI: 10.1002/lt.24037
|View full text |Cite
|
Sign up to set email alerts
|

Experience with molecular adsorbent recirculating system treatment in 20 children listed for high‐urgency liver transplantation

Abstract: For more than 10 years, children at our national center for pediatric liver transplantation (LT) have been treated with Molecular Adsorbent Recirculating System (MARS) liver dialysis as a bridging therapy to high-urgency LT. Treatment was reserved for 20 patients with the highest degrees of hepatic encephalopathy (HE; median grade 5 3.5). Death from neurological sequelae was considered imminent for these patients, and this was further reflected in significantly higher international normalized ratios and ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 43 publications
0
39
0
1
Order By: Relevance
“…Oral and IV formulations appear equally effective (246) The use of liver assist devices such as molecular adsorbent recirculating systems ( MARS) or plasma exchange have proven effective as a bridge to transplant, but remain largely investigational (68,69,(251)(252)(253). The role of nanotechnology to deliver hepatoprotective agents to the liver promise for the future (67).…”
Section: Treating Dilimentioning
confidence: 99%
“…Oral and IV formulations appear equally effective (246) The use of liver assist devices such as molecular adsorbent recirculating systems ( MARS) or plasma exchange have proven effective as a bridge to transplant, but remain largely investigational (68,69,(251)(252)(253). The role of nanotechnology to deliver hepatoprotective agents to the liver promise for the future (67).…”
Section: Treating Dilimentioning
confidence: 99%
“…Randomized clinical trials using the Molecular Adsorbent Recirculating System (MARS) have shown significant dialysis effects with a considerable reduction in serum ammonia, bilirubin and bile acids along with a slight improvement in hepatic encephalopathy. However, all these large clinical trials have failed to demonstrate any survival benefit for the patients treated with MARS111213.…”
mentioning
confidence: 99%
“…MARS was applied for eight consecutive hours daily, every day, up until transplantation. All patients were mechanically ventilated and on vasopressors [10], as was the case in our patient. This method decreased serum ammonia and bilirubin [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although MARS dialysis is the most extensively studied type of ELS, it is limited to case reports and small case series [10]. …”
Section: Introductionmentioning
confidence: 99%